PENGARUH KUALITAS PRODUK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE SAMSUNG (Studi Kasus Pada Desa Pabuaran) - Therdi Alnando; Joan Yuliana Hutapea (Jurnal Ekonomis, 2021)
The purpose of this study was to determine the effect of product quality and promotion on purchasing decisions for Samsung smartphones taken from questionnaires distributed to the Pabuaran village community. The data collection technique used purposive sampling predetermined sample criteria, namely the Pabuaran village community who had seen the advertisement and had purchased Samsung mobile phone products. From these results partially product quality has a significant effect on purchasing decisions. Supported by a t test of 9.251 t > 1.981 table results and obtained a significant result of 0.000. Promotion partially also affects purchasing decisions. This is supported by the t-test results of 4.840 > table results of 1.981 and significant results of 0.000. Simultaneously, product quality and promotion variables affect purchasing decisions. this statement with the results of the f test Fcount 136,709 > F table value: 3.08 and 0.000 <0.05.